ANALISIS TERHADAP ISTBAT NIKAH OLEH ISTRI YANG DI POLIGAMI SECARA SIRRI (Studi Putusan Mahkamah Syar’iah Nomor: 206/Pdt.G/2013/MS.Sgi) - EKO PERMANA DALIMUNTHE (PREMISE LAW JURNAL, 2016)
Seen from its form, a marriage has many varieties; but in Indonesia, a legal marriage in the Law on Marriage and in the KHI (Compilation of the Islamic Laws) is monogamy and polygamy. The research used descriptive analytic and judicial normative methods or judicial literature research. The result of the research showed that a marriage istbat filed by a wife, whose husband is a polygamist by sirri marriage, is not found in KHI which only permits a marriage istbat on condition as follows: first, the marriage occurs in the process of divorce; secondly, the marriage book is missing; thirdly, there is a doubt whether one of the marriage requirements is valid or not; fourthly, a marriage has occurred before Law No. 1/1974 was in effect; fifthly, a marriage which is done by those who have no problem with the marriage itself according to Law No. 1/1974 (according to Article 7, paragraph 3 of KHI). Keywords: Marriage Istbat, Marriage in Polygamy, Verdict